ANALYSIS OF THE ATTITUDE OF THE SOVIETS TO MOSQUES IN UZBEKISTAN (Scientific journal of the Fergana State University, 2024)
In the article the author analyses the Soviet government’s double-sided policy in Islam and masjids, laws and decrees on this sphere attracting archive materials.